Mengurai Lapisan Naratif: Suatu Analisis Naratologis terhadap Tense, Mood, dan Voice dalam Where the Crawdads Sing (2018) karya Delia Owens - Legesang, Jaldrayana Elisabeth (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2025)
Unfolding Through Layers: A Narratological Analysis of Tense, Mood, and Voice in Where the Crawdads Sing (2018) by Delia Owens examines the narrative structure of the novel through Gérard Genette’s narratological framework. The study aims to identify the narrative tense, mood, and voice and to analyze their implementation in the novel. Using a qualitative descriptive method, the study identifies and classifies narrative passages according to Genette’s theory. The findings reveal that the narrative tense in the novel is structured through anachronic order involving analepsis and prolepsis, various narrative durations such as scene, summary, pause, and ellipsis, and multiple frequencies including singulative, repetitive, iterative, and anaphoric. In terms of mood, the narration primarily employs internal focalization while also incorporating zero and external focalization. In terms of voice, the narrative is characterized by subsequent narration, an extradiegetic level, and a heterodiegetic narrator. Through the identification and analysis of the implementation of these narratological elements, the study demonstrates how Owens constructs a layered and non-linear narrative that organizes time (tense), perspective (mood), and narrative stance (voice).